Tiahuanaco ¿cultura o estado? - Onque Suaña, Marisa Jimena (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2023)
The present work aims to demonstrate that the Tiahuanaco culture is one of the most important civilizations of the Andes, so that it can be considered a state due to its form of organization and expansion. In addition, the Tiahuanaco civilization managed to bring its culture in a material andideological way to different peoples in its region. Specifically, with the research process, following a chronological order, and with the support of instruments or bibliographic data, we are going to substantiate that Tiahuanaco is a State, since it has the basic elements that guarantee the existence of any State: Territory, Society or people. And power.